RULE OF REASON AND PER SE ILLEGAL APPROACHES IN ENFORCING THE BUSINESS COMPETITION LAW - Ahmad, Sufmi Dasco (Yustisia, 2017)
AbstractThis article aimed to find out and to give solution to the application of rule of reason and per se illegal approaches in solving the case of monopoly infringement and unfair  business competition. This study was a doctrinal research with evaluative research form. The analysis used was deductive logic one. Per se illegal approach used by KPPU in making decision was based on deliberation and focused more on business behavior than on market situation. This rule of reason approach was an approach constructed based on an assumption that the high sale concentration in the presence of certain agreement between some business performers tend to result in substantial economic efficiency. Essentially, this rule of reason approach considered its economic benefit more than imposed restriction (prohibition). Standard rule of reason allows for the consideration of competitive factors and the determination of the feasibility of trading constraint. The recommendation of research was that: The use per se illegal and/or rule of reason in KPPU’s verdict should build on the objective of the development of Law No.5 of 1999, particularly the provision of Article 3, thereby can realize conducive business climate in the certainty of equal business opportunity for large, medium, and small scale employers, and the achievement of effective and efficient business activity. The application of per se illegal or rule of reason approaches in KPPU’s verdict was possible through the use of two approaches all at once, recalling very extreme difference of per se illegal and the rule of reason, and furthermore, most KPPU’s decision put its position between the two perspectives.Keywords : Per Se Illegal, the Rule of Reason, Monopoly, Unfair Business Competition